The relative roles of portal hypertension and of cirrhosis in the pathogenesis of pulmonary lesions associated with chronic liver disease - O'Brien, John A (UCT/MRC Liver Research Centre, 2017)
There have been numerous reports of cardiovascular and pulmonary abnormalities in patients with cirrhosis and portal hypertension. The role of portal hypertension in the pathogenesis of pulmonary abnormalities in patients with liver disease has not been defined. The present study was therefore undertaken to clarify this. Pulmonary function, including exercise testing, was evaluated in two groups of patients, 11 with portal hypertension due to cirrhosis and 10 with extrahepatic portal vein thrombosis and normal liver histology. Carbon monoxide gas transfer (TLCOsb) was less than 75% of predicted values in four patients from each group. One patient from each group had clinical and catheter confirmed evidence of pulmonary hypertension. Abnormal cardiorespiratory responses to exercise occurred in three patients in the extrahepatic group. Two had associated low TLCOsb and one developed arterial desaturation on exercise. A similar pattern was seen in three patients with cirrhosis. All had low TLCOsb and one developed arterial desaturation during exercise. In the cirrhotic group however three additional patients showed reduction in Pa02 unassociated with elevated heart rate response on exercise. There was no significant correlation with the presence of autoimmune antibodies which appear to be a secondary phenomenon. Our results suggest that pulmonary hypertension is linked to the presence of portal hypertension. Reduction in arterial P02, appears to occur only in patients with liver disease, presumably on the basis of intrapulmonary shunting.